The influence of mirror exposure on weight-related health behaviors: physical activity and food selection - Hodgin, Katie L., author; Graham, Daniel, advisor; Bellows, Laura, committee member; Fisher, Gwenith, committee member; Harman, Jennifer, committee member (Colorado State University. Libraries, 2017)
In terms of Objective Self-Awareness (OSA) theory, heightened focus on the self leads individuals to align their behavior with a personally- or socially-derived standard. Exposure to a mirror may increase self-awareness and has previously been found to induce behaviors that align with a known or implied standard, such as honesty and helping behavior. However, very little research has investigated the influence of mirror exposure on health behaviors, which are commonly valued. The present research describes two studies examining the effects of mirror exposure on the health behaviors of stair vs. elevator use and food selection, hypothesizing that individuals exposed to a mirror prior to one of these health choices would be more likely to take the stairs instead of the elevator and to select more healthful food products (i.e., lower in calories, saturated fat, sugar, and sodium), respectively. University students (n = 204 for stair use and n = 79 for food selection) were observed as they chose to take the stairs or elevator to the fourth floor of a campus parking garage or after they selected four food items from a laboratory-turned-grocery aisle, and then were surveyed on demographic information and their behaviors likely linked with physical activity and healthy eating. Results indicate that participants' odds of stair use were increased after exposure to a body-length mirror with a health sign describing caloric expenditure during stair use (OR = 2.99, p = 0.06, 95% CI: 0.96, 9.31) and after exposure to a social norm sign on its own (i.e., without a mirror) describing the high stair use of university students (OR = 3.63, p = 0.02, 95% CI: 1.21, 10.94). Neither body-length nor small mirrors showing only the face were found to predict the mean caloric, saturated fat, sugar, or sodium content of participants' selected food items. Implications of these findings regarding weight-related health behaviors are discussed in the context of OSA theory and mirror exposure for health promotion.